2019
DOI: 10.1039/c9cp05028k
|View full text |Cite
|
Sign up to set email alerts
|

Integration of thermo-electrochemical conversion into forced convection cooling

Abstract: Forced convection cooling is important in numerous technologies ranging from microprocessors in data centers to turbines and engines; active cooling is essential in these situations. However, active transfer of heat or thermal energy under a large temperature difference promptly destroys the exergy, which is the free-energy component of thermal energy, and this issue has remained unaddressed. Herein, we describe a thermoelectrochemical conversion to partially recover presently lost exergy in forced convection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Both the power generation density and cooling efficiency at the heat-releasing surface are important performance measures of such a combined-purpose system. Thus far, previous studies, including ours, reported power densities of 0.25, 22 0.05, 23 0.36, 28 and 0.44 29 W m −2 along with heat transfer coefficients, which are a measure of cooling efficiency (given by eqn (2) later), of 450 23 and 620 29 W m −2 K −1 . While the latter values were moderate, 36 the power densities were too low for this concept to be considered feasible.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Both the power generation density and cooling efficiency at the heat-releasing surface are important performance measures of such a combined-purpose system. Thus far, previous studies, including ours, reported power densities of 0.25, 22 0.05, 23 0.36, 28 and 0.44 29 W m −2 along with heat transfer coefficients, which are a measure of cooling efficiency (given by eqn (2) later), of 450 23 and 620 29 W m −2 K −1 . While the latter values were moderate, 36 the power densities were too low for this concept to be considered feasible.…”
Section: Introductionmentioning
confidence: 54%
“…1a) has been unexplored, except for a few previous works that reported limited power densities of only 0.05−0.5 W m −2 . 22,23,28,29 Such a concept is inherently challenging because of the necessity of simultaneously designing the fluid dynamics, heat transfer, and ion transport in the non-isothermal channel region through which the electrolyte passes, where the latter also acts as a coolant. Therefore, optimal design of the flow in the channel region and choice of the electrolyte liquid, as well as optimal choice of materials to favour green and durable systems, are crucial to render this concept feasible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations